Sustainable Urban Transformation: Is it possible to improve walkability and cyclability in cities through data-science driven methods? - Sanchez-Sepulveda, Monica V.; Navarro, Joan; Fonseca Escudero, David (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
Some of the negative effects of rapid urban growth in recent decades include increased traffic and a lack of infrastructure for pedestrians and cyclists. The research project called “Acciona y Conecta,” carried out in the city of Barcelona, aims to answer the research question: how can walkability and cyclability in cities be quantified and improved? The research hypothesis driving the project is that data science and other advanced technologies can transform urban infrastructure, leading to more mobile, healthier, and sustainable cities. To achieve this, an assessment of mobility in Barcelona has been conducted, a database has been created, several urban improvement proposals have been developed, and this methodology has been replicated in other cities (Madrid and Helsinki), while also promoting citizen participation. This work presents the latest developments and findings of the research project regarding urban structure assessment, identification of urban planning parameters for quantitative analysis, urban planning recommendations, and scalability to other environments.